UNDERSTANDING OF INDONESIAN VOCATIONAL STUDENTS SELF-EFFICACY BELIEF IN LEARNING ENGLISH SPEAKING - Maulidia Maulidia; Muhammad Zuhri DJ (Institut Agama Islam Negeri Parepare, 2023)
This research aims to find out the level of self-efficacy beliefs of eleventh graders at SMKN 7 Bone. This research method uses descriptive quantitative methods by means of an instrument that gives students a questionnaire about self-efficacy beliefs. This research used a purposive sampling technique involving 20 students from the hospitality department as the sample. Data collection is done by giving directions to students, distributing questionnaires to students, and collecting all the questionnaires that have been answered by students. Data were analyzed by means of preparation, tabulation, and implementation. The levels of self-efficacy belief are divided into very low, low, medium, high, and very high. Once collected, the data is calculated, and the results are converted into percentages (%). The results obtained from this research show that the magnitude dimension gets an average score of 3, the generality dimension gets an average score of 3.04, the strength dimension gets an average score of 3, and overall this research gets an average score of 3.01. From these results, it is converted into a percentage of the value, which is 75.25%, which indicates a high level. With the results of the research, it was concluded that the level of self-efficacy belief of eleventh graders at SMKN 7 Bone is on average high.